Efeitos do tratamento com cúrcuma e exercício resistido no tecido muscular estriado esquelético em modelo de artrite reumatoide - Jesus, Maiara Cristina Lima de (2024)
Rheumatoid arthritis (RA) is a chronic, inflammatory, systemic disease affecting approximately 1% of the global population. Its symptoms include joint pain, swelling, and stiffness, leading to muscle weakness and functional impairments. Early diagnosis and treatment are crucial to prevent deformities and disabilities. Standard treatment involves nonsteroidal anti-inflammatory drugs and glucocorticoids, which alleviate symptoms but can cause undesirable side effects and are costly. Consequently, alternative therapies such as phytotherapy and therapeutic exercises, like turmeric, which has anti-inflammatory properties and reduces free radicals in inflammatory conditions such as RA, have been explored. On the other hand, resistance exercises can reduce pain, promote muscle hypertrophy, stimulate satellite cell proliferation, and effectively reverse rheumatoid sarcopenia while improving function. Therefore, investigating therapies with minimal side effects, accessibility, and low cost is important. This study evaluated the morphofunctional effects of turmeric supplementation combined with resistance exercise on skeletal muscle tissue in an RA model. Forty-two Wistar rats, averaging 15 weeks old, were divided into 7 groups (n=6): control group (CG); turmeric group (TG); exercise group (EXG); rheumatoid arthritis group (RAG); arthritis + turmeric group (RA+TG); arthritis + exercise group (RA+EX); arthritis + turmeric + exercise group (RA+TG+EX). RA induction began on day one with a 50 µL injection of Freund's Complete Adjuvant (CFA) at the tail base, followed by a repeat dosage in the right tibiofemoral joint after 7 days. Turmeric treatment (100 mg/kg/day of curcumin dry extract) started 24 hours post-intra-articular induction and continued for 15 days. Stair climbing exercise was performed on alternate days for 7 days. Functional assessments included joint swelling, grip strength, paw elevation time (PET), and nociceptive threshold. Baseline evaluations were conducted on day one, followed by four assessments at 4-day intervals post intra-articular induction. On day 24, animals were euthanized, synovial fluid from the tibiofemoral joint and gastrocnemius muscle were collected and processed for light microscopy analyses. Data were analyzed using SPSS 20.0® software with generalized linear models, LSD post-tests, and a significance level set at 5%. CG, TG, and EXG groups exhibited lower mean leukocyte counts in synovial lavage analysis (p<0.02) and arthritis index (p<0.001) compared to arthritis-induced treated groups, with RA+TG+EX showing the lowest means compared to isolated treatment groups (p<0.01). Functional analysis revealed higher mean nociceptive thresholds (p<0.02) and greater grip strength (p<0.001) in CG, TG, and EXG at AV1; CG and EXG showed lower mean PET compared to arthritic groups (p<0.05). Histopathological evaluation showed greater joint impairment in arthritic groups, with the combined treatment group (TG+EX) exhibiting fewer changes similar to TG and EXG. Histomorphometry indicated RAG had more fibers (p<0.05), denoting muscle atrophy, and more capillaries (p<0.02), indicating angiogenesis. CG, TG, and EXG had larger mean areas (p<0.04); EXG showed increased major (p<0.02) and minor diameters (p<0.01), indicating muscle hypertrophy. The combined group (RA+TG+EX) showed results similar to control groups, indicating turmeric supplementation and resistance exercise promoted skeletal muscle tissue recovery and improved morphofunctional parameters. In conclusion, combined treatment proved effective in managing RA in this study.